2019
DOI: 10.1038/s41598-019-55934-w
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion to collagen promotes leukemia resistance to doxorubicin by reducing DNA damage through the inhibition of Rac1 activation

Abstract: Chemoresistance is a major hurdle in anti-cancer therapy. Growing evidence indicates that integrin-mediated cell adhesion to extracellular matrix plays a major role in chemoresistance. However, the underlying mechanisms are not fully understood. We have previously shown that the collagen-binding integrin α2β1 promoted doxorubicin resistance in acute T cell lymphoblastic leukemia (T-ALL). In this study, we found that acute myeloid leukemia (AML) cell lines also express α2β1 integrin and collagen promoted their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…Implication of α2β1 integrin in tumor progression and metastasis was reported in several other types of cancers, including pancreatic, colorectal, gastric and lung cancers, oral squamous cell carcinoma and T-cell acute lymphoblastic leukemia, which were previously reviewed in ( 319 ). Lastly, it has been reported that α2β1 integrin and collagen I participate to doxorubicin-induced drug resistance in leukemia by either protecting leukemia cells from apoptosis through MAPK/ERK pathway activation ( 317 ), or by decreasing the DNA damage through the inhibition of Rac1 activation ( 318 ).…”
Section: Collagen-binding Integrins In Cancermentioning
confidence: 99%
“…Implication of α2β1 integrin in tumor progression and metastasis was reported in several other types of cancers, including pancreatic, colorectal, gastric and lung cancers, oral squamous cell carcinoma and T-cell acute lymphoblastic leukemia, which were previously reviewed in ( 319 ). Lastly, it has been reported that α2β1 integrin and collagen I participate to doxorubicin-induced drug resistance in leukemia by either protecting leukemia cells from apoptosis through MAPK/ERK pathway activation ( 317 ), or by decreasing the DNA damage through the inhibition of Rac1 activation ( 318 ).…”
Section: Collagen-binding Integrins In Cancermentioning
confidence: 99%
“…Such quantitative differences in the release of extracellular regulators may contribute to the previously described differences among various stem cell niches in their regulation of normal hematopoiesis [ 3 ]. Many of the extracellular regulators involved in normal hematopoiesis are also important in leukemic hematopoiesis although their function in leukemic hematopoiesis is less well characterized; e.g., collagen/integrin/Rac1 [ 56 , 57 ], the CDH1 [ 58 ] and CDH2 cadherins [ 59 ], thrombospondin [ 60 , 61 ], TGFβ [ 62 , 63 , 64 ], osteopontin [ 65 ] and LOX/lipid metabolism [ 66 , 67 ] all seem to be important for leukemogenesis and/or chemosensitivity in hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…a 2 b 1 mediated adhesion activates the MAPK/ERK pathway, which inhibits the doxorubicin-induced activation of c-Jun N-terminal kinase (JNK) and maintains the pro-survival protein Bcl-2 family member Mcl-1. The same group extended a 2 b 1-collagen mediated doxorubicin resistance in the AML cell lines HL-60 and U937 (165). In AML, collagen binding through a 2 b 1 inhibited the activation of the pro-apoptotic protein Rac1, thereby preventing Rac1 induced DNA damage.…”
Section: Integrin a 2 (Cd49b)mentioning
confidence: 93%
“…Integrin a2b1 binds to collagen and upregulates ABCC1 via the ERK/MAPK pathways to modulate efflux (221). Similarly, collagen-binding b1 integrins contribute to doxorubicin resistance in AML by reducing DNA damage through Rac1 inhibition (222).…”
Section: Integrin B1 (Cd29)mentioning
confidence: 99%